PENEGAKAN HUKUM TERHADAP PENELANTARAN ANAK DI KABUPATEN KENDAL - Wijayati, Safriena Rudy; Listyarini, Dyah (LPPM STIH Awang Long, 2023)
Abandoned children is a child who has not yet turned 18 (eighteen) years old and for some reason one or both parents are unable to fulfill their child's rights to grow and develop, then in the end they became abandoned. Article number 34 section one (1) of the 1945..Constitution of Republic Indonesia..states that